Interleukin-10 modulates type I collagen and matrix metalloprotease gene expression in cultured human skin fibroblasts. - Reitamo, S (1994)
IL-10, originally isolated from mouse helper T cells, is a cytokine with regulatory functions on a number of interleukins. In this study we show that recombinant human IL-10 affects the expression of several genes involved in extracellular matrix synthesis and remodeling in human dermal fibroblast cultures. As judged by Northern blot analyses, type I collagen gene expression was downregulated, while collagenase and stromelysin gene expression were markedly enhanced by IL-10. No effect on tissue inhibitor of metalloproteases mRNA levels was noted. Transient transfections of skin fibroblasts with type I collagen promoter/chloramphenicol acetyl transferase reporter gene constructs showed downregulation by IL-10, suggesting inhibition at the transcriptional level. When compared with control cultures, incubation with IL-10 resulted in a decrease in immunostaining of fibroblast cultures with antibodies to human type I collagen. In contrast, immunostaining of such IL-10-treated cultures with antibodies to human collagenase resulted in an increase in immunostaining. This study suggests a role for IL-10 in the breakdown and remodeling of the extracellular matrix.